Pengelolaan Pertanian Berkelanjutan Berbasis Eco-spirituality Dalam Tradisi Komunitas Adat Dan Implikasinya Terhadap Ketahanan Cultural Socio-Ecological System (Studi Pada Tradisi Komunitas Adat Di Tajakembang, Cilacap, Jawa Tengah) - Sudarto, Sudarto; Wijayanti, Yeni; Pramesti, Cipto Surya; Agustina, Deden Dendi (Jurnal Ketahanan Nasional, 2024)
This research discussed eco-spirituality in the tradition of the Tajakembang, Cilacap indigenous community, with a focus on sustainable agricultural management and cultural socio-ecological system resilience.Using an ethnographic approach and qualitative analysis, this study illustrated how these communities integrated spiritual and Islamic values in their agricultural practices, thereby creating a sustainable and resilient agricultural system, referring to the development of a harmonious relationship between humans and nature, as well as the integration of Islamic values oriented towards environmental balance. The application of community resilience theory and social practice theory in this study provided a critical perspective to analyzed the dynamic interaction between structures and agencies in social relations.This research contributed to the understanding of eco-spirituality in indigenous community traditions, by emphasizing its role in sustainable agricultural management, resilience of cultural socio-ecological system and the integration of various values. Cultural socio-ecological system resilience refered to the ability of communities to adapted and to survived in the face of environmental and social changes. Eco-spirituality values strengthened the resilience of the Tajakembang indigenous community, for example, the practice of sharing resources and traditional knowledge could increase the community's adaptation capacity to climate change.